Conditional legitimacy: How turnout, majority size, and outcome affect perceptions of legitimacy in European Union membership referendums. (June 2019) - Arnesen, Sveinung; Broderstad, Troy S; Johannesson, Mikael P; Linde, Jonas
This conjoint study investigates the type of mandate a referendum confers in the political decision-making process. While a majority of citizens in general believe that the government should follow the results of a referendum on European Union membership, its perceived legitimacy in the eyes of the public heavily depends upon the level of turnout, the size of the majority, and the outcome of the specific referendum in question. Thus, whether a referendum legitimizes a political decision in the eyes of the public is conditional upon these three dimensions.